काष्ठमण्डपभित्र रहेका प्रतिमाहरूको विवादबारे विश्लेषणात्मक अध्ययनAn Analytical Study of the Controversy of the Images Inside the Kastamandapa - रन्जितकार Ranjitkar जुनुमैया बासुकला Junumaiya Basukala (Patan Prospective Journal, 2022)
Available with fulltext.